Inflation, fiscal policy and inequality - Antonio F. Amore; Henrique S. Basso; Johannes Simeon Bischl; Paola De Agostini; Silvia De Poli; Emanuele Dicarlo; Maria Flevotomou; Maximilian Freier; Sofia Maier; Esteban García-Miralles; Myroslav Pidkuyko; Mattia Ricci; et al. (European Commission, Joint Research Centre (JRC), 2023)
This paper analyses the distributional impact of high consumer inflation in the euro area and government measures to compensate households in 2022. The study uses the tax-benefit microsimulation model for the European Union (EUROMOD) with microdata as the input - EU statistics on income and living conditions (EU-SILC) and household budget surveys (HBS) - to quantify the distributional impact of inflation, income support measures and measures aimed at containing prices. The analysis confirms that purchasing power and welfare were more severely affected by the 2022 inflation surge in lower-income households than in higher-income households. Fiscal measures compensated households for about a third of their welfare loss, though with significant differences between countries. At the same time, fiscal measures closed around 60% of the inequality gap between lower and higher-income households. Most fiscal measures were not particularly well targeted at low-income households, resulting in a higher than necessary fiscal burden to cushion the distributional impact of the inflationary shock.
Keywords: 330